Nutrient Digestibility and Performance of Male Pelung Chicken Fed Rice Bran-Based Ration Supplemented with Lime (Citrus aurantifolia) Juice - Istna Mangisah; B Sukamto; H. I. Wahyuni; I. Estiningdriati; W. Saputro; L. Krismiyanto (Media Peternakan, 2016)
Rearing Pelung chicken in Indonesia, in general, uses a ration with a high proportion of rice bran, even up to 60%. Considering the high contents of fiber, lignin, and phytic acid, feeding a high portion of rice bran will decrease nutrient digestibility. This study was aimed to evaluate the effect of lime juice supplementation of a rice bran-based ration on the utilization of nutrients in male Pelung chicken. Sixty four of 12 weeks old male Pelung chickens were used in the present experiment and assigned into a completely randomized block design. The treatments were supplementation of the ration with lime juice at the levels of 0, 1, 2, and 3 mL/100 g. Parameters measured were feed and nutrients consumption, protein, fat, and fiber digestibilities, apparent metabolizable energy (AME), rate of passage, feed conversion ratio (FCR), and daily body weight gain. The results showed that  the supplementation of lime juice in the ration did not affect feed and nutrient consumption, but significantly (P<0.05) increased the digestibilities of protein, fat and fiber, AME, rate of passage, FCR and daily body weight gain. However, supplementation  of 2 or 3 mL lime juice in the ration resulted in similar values of AME, and protein, fat and fiber digestibilities, and both levels of supplementation produced better protein and fat digestibilities, and AME when compared to the other treatments. It could be concluded that supplementation of 3 mL lime juice in the ration increased the digestion processes in the gastrointestinal and increased daily weight gain of male Pelung chicken.